Complexity signatures for short time scales in the atmosphere above Adventdalen, Svalbard. Issue 2 (30th January 2014) - Hall, C. M.
Abstract Atmospheric parameters from the troposphere above Adventdalen, Svalbard, 78°N, 16°E, are examined for signatures of complexity in their respective stochastic components over time scales from 1 h to 1 year. Several approaches are used, all of which can estimate values of the generalized Hurst exponent, α, which can in turn be compared with each other and with similar independent characterizations, usually via the classic Hurst exponent, H, obtained from location‐specific and globally averaged time series. For tropopause altitude, the stochastic component exhibits the signature of a persistent fractional Gaussian noise (fGn) with α ≈ 0.75. For surface air temperature, the indications are for fractional Brownian motion (fBm) with α ≈ 1.4. Using recent high time‐resolution data from a single high‐latitude location, this identification of fBm is relevant for short‐term memory as opposed to findings from many other studies addressing possible long‐term memory, which demonstrate fGn with α = H ≈ 0.7. Furthermore, the lack of similarity between the results for surface air temperature and tropopause altitude suggests that different underlying processes are responsible for stochastic variability.